2000
DOI: 10.7326/0003-4819-132-3-200002010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Relation between HIV and Invasive Pneumococcal Disease in San Francisco County, California

Abstract: In a community with a high prevalence of HIV infection, much of the burden of pneumococcal disease was attributable to AIDS. High incidence rates were seen in young adults and especially in black persons. Efforts to increase pneumococcal vaccination rates should target HIV-infected adults, particularly those living in poor urban areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
100
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(113 citation statements)
references
References 26 publications
8
100
0
5
Order By: Relevance
“…Rates of invasive pneumococcal infection among HIV-infected patients may be as much as 100-fold greater than among HIV-negative controls in the absence of highly active antiretroviral therapy (HAART) [1]. Although cohort or population-based surveillance studies suggest that the incidence of invasive pneumococcal infections or pneumococcal pneumonia declines among HIV-infected patients with access to HAART and appropriate antimicrobial prophylaxis [2,4,6,7], it remains significantly higher among HIV-infected patients than in the general population, with risk ratios ranging from 35 to 60 [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rates of invasive pneumococcal infection among HIV-infected patients may be as much as 100-fold greater than among HIV-negative controls in the absence of highly active antiretroviral therapy (HAART) [1]. Although cohort or population-based surveillance studies suggest that the incidence of invasive pneumococcal infections or pneumococcal pneumonia declines among HIV-infected patients with access to HAART and appropriate antimicrobial prophylaxis [2,4,6,7], it remains significantly higher among HIV-infected patients than in the general population, with risk ratios ranging from 35 to 60 [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HIV infection are at significantly higher risk for invasive infection with Streptococcus pneumoniae as compared with persons without HIV infection [1][2][3][4][5]. Rates of invasive pneumococcal infection among HIV-infected patients may be as much as 100-fold greater than among HIV-negative controls in the absence of highly active antiretroviral therapy (HAART) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a decrease in the incidence of bacterial pneumonia and invasive pneumococcal disease (IPD) in HIV-infected patients that was mainly associated with the introduction of HAART [2][3][4][5] and 7-valent pneumococcal conjugate vaccine (PCV7) for children [6]. However, the incidence rates of IPD in HIVinfected patients remain high [7,8] and a recent population-based study from Denmark showed that the incidence of overall pneumonia in HIV-infected patients remains higher than in the general population [9].…”
Section: Introductionmentioning
confidence: 99%
“…19 Despite cART, the risk of pneumococcal disease remains elevated for HIV-infected persons compared with HIV-uninfected persons (10-60-fold). 19,[21][22][23][24][25] Although these studies were mainly conducted in the early cART era consisting of HIVinfected patients with CD4 cell counts <200 cells/ml, a recent study in the UK, in which more than 80% of HIV-infected adults with a CD4 cell count <350 cells/ml were receiving cART, still reported a 20-time higher risk of IPD among HIVinfected adults compared to the general population. 25 Therefore, other preventive interventions for pneumococcal disease are necessary among HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%